Analysis of Risk Factors for Normal Glucose Tolerance-Hyperinsulinemia - Nie, MD, Lei; Zhong, MD, Zhibiao; Ai, MD, Wei; Yu, MD, Ming; Li, MD, Lian; Ye, MD, Xiaoman; Chi, MD, Lianxiang (North American Journal of Medicine and Science, 2018)
The aim of this paper is to study the prevalence of individuals with normal glucose tolerance-hyperinsulinemia in Nanshan of Shenzhen, determine the cut point values of normal glucose tolerance-hyperinsulinemia, and investigate the risk factors for it. All subjects were followed 75g oral glucose tolerance test (OGTT) and insulin releasing test. Glucose metabolic disorders were determined according to WHO definition (1999). Hyperinsulinemia was determined if fasting serum insulin and/or 2-hour serum insulin ≥ the 90th percentile, so subjects with normal glucose tolerance were divided into two groups: hyperinsulinemia and normoinsulinemia. The islet cell function and metabolic characteristics of individuals with normal glucose tolerance-hyperinsulinemia were analyzed and its related risk factors were investigated by Logistic regression analysis. The cut point values of normal glucose tolerance-hyperinsulinemia in Nanshan of Shenzhen is fasting serum insulin ≥ 13.85 mU/L and/or 2-hour serum insulin ≥ 74.97 mU/L. The prevalence of NGT- HINS in the community was 7.84%. The differences of the prevalence of high blood, HDL, LDL, TG, UA were significant between subjects with NGT-HINS and NGT-NINS (P < 0.05); and the differences are nonsignificant between subjects with NGT-HINS and IGR (P > 0.05). There were significant differences on 2hPG between subjects with NGT-HINS and IGR (P < 0.05), and no difference between individuals with NGT-HINS and NGT-NINS (P > 0.05). The differences of the smoking rates, Baecke index, BMI, WHR, TC, FPG, HbA1C, HOMA-IR, and HBCI/R were significant among these groups. There were nonsignificant differences on age, sex, drinking rate among three groups (P > 0.05). Logistic regression analysis showed that BMI (OR = 14.019, 95% CI: 4.111, 47.800; P = 0.000); TG (OR = 9.336, 95% CI: 2.697, 32.313; P = 0.000); HDL (OR = 0 .181, 95% CI: 0 .053, 0.625; P = 0.007); FPG (OR = 5.276, 95% CI: 1.588, 17.535; P = 0.007); HOMA-IR (OR = 22.727, 95% CI: 6.895, 74.915; P = 0.000); HBCI/IR (OR = 6.611, 95% CI: 2.238, 19.529; P = 0.001) were the independent predictors for NGT-HINS. Our results show that the cut point values of normal glucose tolerance-hyperinsulinemia in Nanshan of Shenzhen is fasting serum insulin ≥ 13.85 mU/L and/or 2-hour serum insulin ≥ 74.97 mU/L. Individuals with NGT-HINS suffered more metabolic risk factors and had a decreased β-cell function. NGT-HINS is a transitional state between NGT and IGR. BMI, TG, HDL, FPG, HOMA-IR, and HBCI/IR were the independent predictors for NGT-HINS. [N A J Med Sci. 2018;11(1):43-51. DOI: 10.7156/najms.2018.1101043]